2017
DOI: 10.1103/physrevb.96.184201
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal growth and study of the mixed spin-dimer system Ba3xSrxCr2

Abstract: The compounds Sr 3 Cr 2 O 8 and Ba 3 Cr 2 O 8 are insulating dimerized antiferromagnets with Cr 5+ magnetic ions. These spin− 1 2 ions form hexagonal bilayers with a strong intradimer antiferromagnetic interaction that leads to a singlet ground state and gapped triplet states. We report on the effect on the magnetic properties of Sr 3 Cr 2 O 8 by introducing chemical disorder upon replacing Sr by Ba. Two single crystals of Ba 3−x Sr x Cr 2 O 8 with x = 2.9 (3.33% of mixing) and x = 2.8 (6.66% of mixing) were g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Recently, we showed that introducing Ba in the Sr 3 Cr 2 O 8 system does lead neither to magnetic disorder nor to intragap intensities in the dispersion relation [19]. The Jahn-Teller distortion temperature in Ba 3−x Sr x Cr 2 O 8 is gradually suppressed with decreasing x, as shown in Ref.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Recently, we showed that introducing Ba in the Sr 3 Cr 2 O 8 system does lead neither to magnetic disorder nor to intragap intensities in the dispersion relation [19]. The Jahn-Teller distortion temperature in Ba 3−x Sr x Cr 2 O 8 is gradually suppressed with decreasing x, as shown in Ref.…”
Section: Resultsmentioning
confidence: 84%
“…6) as well as the ratio of interto intradimer interaction J /J 0 with x. In fact it was found that for Ba 3 Cr 2 O 8 this ratio is slightly larger (J /J 0 = 0.82) than for Sr 3 Cr 2 O 8 (J /J 0 = 0.64) [19]. This subtle difference could be the reason for the fundamentally different dynamics.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, we reported on the effect of chemical substitution on the magnetic properties of Ba 3−x Sr x Cr 2 O 8 upon partially replacing Sr by Ba by 3.3% and 6.6%. It was found that the intradimer spin-spin interaction is smaller in the mixed compound with x = 2.9 than in pure Sr 3 Cr 2 O 8 by 4%, whereas the interdimer exchange interactions are reduced by 7% [17]. No sign of magnetic disorder was found.…”
Section: Introductionmentioning
confidence: 90%